THE USE OF VIDEO IN TEACHING GRAMMAR TO PRE-SECONDARY STUDENTS - Silalahi, Ivo Novita S br; Halimi, Sisilia Setiawati, Dr. (UI Scholars Hub, 2020)
This paper examines the effectiveness of videos as a teaching medium in a pre-intermediate grammar class in Tangerang, Indonesia. This research adopted a quasi-experimental approach with a posttest control group design. Two pre-secondary classes in Tangerang were selected as subjects of the study. Data were obtained from the pretest and posttest, a questionnaire on student perception of video usage in teaching, and interviews. The experimental class was taught using a video while the control class was taught via textbooks. A pretest and a posttest were given to the experimental class. The improvement in scores was then examined using t-test. To compare the learning results of the two groups, a final posttest was conducted on both classes after the lessons. The scores were then examined using the Mann–Whitney test. Results indicated that students who learned from the video achieved higher scores than those who learned from textbooks. The learning-style questionnaire results revealed that learning with videos was enjoyable. Therefore, this medium is highly recommended as a crucial grammar-teaching tool in the classroom.